The reconstruction of L’Aquila, ancients and new devices - Stefano Cecamore (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2015)
The paper intends to submit the outcomes of the research project achieved during my PhD study in History, Representation and Architecture Conservation XXVII cycle, co-ordinated by professor Claudio Varagnoli, at the Department of Architecture, Heritage Division, University ‘G. d’Annunzio’, Chieti-Pescara. The study analyses the urban fabric of the historical centre of L’Aquila highlighting the progressive rarefaction of the local technique knowledge; the building survey of the Angioino site disperses in the numerous modification of building devices carried out from the mid-fourteenth century onward. The assembly of irregular stone layouts and recovery elements followed through with no clear building logics mark the lean geometry in the late Medieval buildings, such as Palazzo Pascali and several other buildings, which have been renovated and expanded over the following centuries. The use of the traditional anti-seismic devices witnesses the workforce awareness of the insufficient tensile strength resistance of the walls, but the typological and formal adaptation of the original Medieval and Renaissance building cells defines the building constructions as extremely complex and vulnerable compared to seismic activities further burdened by recent and misconstrued restoration project.